Determinan Kejadian Stunting di Wilayah Kerja Puskesmas Edison Jaar Tahun 2023: Determinants of stunting incidents in the working area of Edison Jaar Primary Health Center In 2023 - Ladi; Ainun Nisa; Yulianti; Siti Aisyah Solechah (UNIVERSITAS NGUDI WALUYO, 2024)
Stunting is a persistent nutritional issue in children that may begin during pregnancy, leading to impaired growth and resulting in a child's height being lower than expected for their age (dwarfism) (Izwardy, 2020). Stunting is a health concern demanding immediate attention, as emphasized by the Presidential Regulation of the Republic of Indonesia Number 72 of 2021. In Indonesia, stunting in children under five years old poses a substantial public health challenge. This research aims to establish the correlation between determinant factors, including the history of pregnant mothers experiencing chronic energy deficiency (CED), pregnant mothers with anemia, infants born with low birth weight (LBW), and the history of exclusive breastfeeding, with the occurrence of stunting in children aged 24-59 months in the operational area of Edison Jaar Community Health Center. This correlational descriptive study adopts a case-control research design. The sample, comprising 106 participants, was selected using purposive sampling, with 53 cases and 53 controls. Data were analyzed using the chi-square test.The findings revealed that a history of pregnant mothers with CED (p=0.000, OR=6.006, 95% CI=2.191-16.464), a history of pregnant mothers with anemia (p=0.002, OR=4.655, 95% CI=1.843-11.755), a history of babies born with LBW (p=0.000, OR=5.867, 95% CI=2.245-2.915), and a history of exclusive breastfeeding (p=0.000, OR=33.683, 95% CI=11.287-100.522) were associated with stunting in children aged 24-59 months. It is crucial to enhance promotion, education, and health interventions that emphasize the significance of caregiving during the first 1000 days of life for both mothers and children. Improved coordination and advocacy across sectors are also essential to enhance maternal and child health services, addressing risk factors contributing to stunting in toddlers. ABSTRAK Stunting adalah masalah kurang gizi pada anak yang berlangsung lama yang menyebabkan gangguan pertumbuhan anak yaitu tinggi badan anak lebih rendah dari usianya (kerdil) (Izwardy, 2020). Stunting merupakan masalah kesehatan yang perlu segera diatasi (Peraturan Presiden Republik Indonesia Nomor 72 Tahun 2021).Stunting pada anak di bawah lima tahun adalah masalah kesehatan masyarakat yang serius di Indonesia. Penelitian ini bertujuan untuk mengetahui hubungan antara faktor determinan, seperti riwayat ibu hamil kekurangan energi kronis (KEK), riwayat ibu hamil anemia, riwayat bayi berat badan lahir rendah (BBLR), dan riwayat pemberian ASI eksklusif dengan kejadian stunting pada anak usia 24-59 bulan di wilayah kerja Puskesmas Edison Jaar. Penelitian deskriptif korelatif ini menggunakan desain penelitian case control (kasus dan kontrol). Sampel dalam penelitian ini dipilih menggunakan metode purposive sampling dengan jumlah sampel sebanyak 106 yang kemudian dibagi menjadi 53 sampel sebagai kasus dan 53 sampel sebagai kontrol. Data dianalisis menggunakan uji chi-square. Hasil penelitian menunjukkan bahwa riwayat ibu hamil dengan KEK (p=0,000, OR=6,006, 95% CI=2,191-16,464), riwayat ibu hamil dengan anemia (p=0,002, OR=4,655, 95% CI=1,843-11,755), riwayat bayi lahir dengan BBLR (p=0,000, OR=5,867, 95% CI=2,245-2,915), dan riwayat pemberian ASI eksklusif (p=0,000, OR=33,683, 95% CI=11,287-100,522) berhubungan dengan kejadian stunting pada anak usia 24-59 bulan. Promosi, edukasi dan intervensi kesehatan mengenai pentingnya pola asuh dalam 1000 hari pertama kehidupan pada ibu dan anak perlu ditingkatkan. Koordinasi dan advokasi dengan lintas sektor juga perlu diperbaiki untuk meningkatkan pelayanan di bidang kesehatan ibu dan anak agar dapat menangani faktor risiko yang dapat menyebabkan kejadian stunting pada balita.